Moringa oleifera Lam.: uma fonte vegetal de proteínas hipoglicemiantes e hipolipemiantes - Paula, Paulo Carvalho de (2017)
Diabetes mellitus is characterized by chronic hyperglycemia associated with vascular complications, which cause high morbidity and mortality rates. World projections of the increase in the diabetic number have already been done. This reinforces the search for hypoglycemic plant compounds in the perspective of their use on drug formulation for diabetes treatment. In this context, plant proteins have been included in the arsenal of molecules with hypoglycemic potential. The aim of the present work was to obtain hypoglycemic proteins from the seed coat and leaves of Moringa oleifera, a plant native to India. From this species, a protein fraction from the seed coat (Mo-TEG) and a protein from the leaves (Mo-S3) were obtained, both with hypoglycemic effect. Mo-TEG showed a protein yield of 40%, corresponding to 0.66 mg protein/g of seed coat flour. Mo-LPI was able to cross-react with human anti-insulin antibodies. In alloxan-induced diabetic mice, Mo-TEG showed a short-term hypoglycemic effect after intraperitoneal or oral administration, with a higher effect through the first route (72.3% vs 39.6% 5 h after the administration). Also by the intraperitoneal route, Mo-TEG improved the tolerance to orally administered glucose, exhibiting hypoglycemic effect and improvement of the serum lipid profile when administered along 10 days to alloxan-induced diabetic mice. Regarding to protein from M. oleifera leaves, Mo-S3 was purified by DEAE-Cellulose and Sephacryl S-200 chromatography, with a 891.53-fold purification and 1.04% yield. Mo-S3 is a 8.6 kDa protein as revealed by mass spectrometry under native conditions. In addition to the presence of insulin epitopes, Mo-S3 showed hypoglycemic effect after intraperitoneal administration, in a single dose or repeated doses. Conversely, no significant hypoglycemic effect was observed in diabetic mice when Mo-S3 was orally administered. Moreover, Mo-TEG and Mo-S3 showed hypolipidemic effect in diabetic mice. Altogether, these data demonstrate that proteins belong to the set of hypoglycemic molecules of M.oleifera, which allow their insertion in biomedical research in order to produce drugs to treat diabetes.